How to annotate a corpus for research on frames in the language of mathematics - Fisseni, Bernhard; Sarikaya, Deniz; Schröder, Bernhard (Kalbotyra, 2025)
This paper outlines a plan for designing a corpus-linguistic project from which an analysis of frames specific to mathematical proof texts shall be derived. Previous work has already developed instances of frames for mathematical texts. We have argued that these frames are well suited to model how background knowledge enriches explicitly given information. To this end, a collection of mathematical texts needs to be annotated.We describe the idea behind the corpus annotation, frame semantics and how we adapted frames for mathematical texts in particular by distinguishing between structural proof frames and ontological ones. Ontological frames for instance correspond to proof techniques, while structural frames model domain knowledge like exact definitions of mathematical structures. We describe annotation principles, explain qualifications annotators should have and how such annotations can be evaluated.We explain potential linguistic research questions: The corpus will allow us to study the linguistic means by which frames are introduced and signaled. We plan to generalize beyond previous case-based analyses and to provide a foundation for broader empirical research on mathematical language and practice. We argue that these can be used in deeper semantic parsing and the development of interactive theorem-proving software. We furthermore assume that this perspective on mathematical text will also have implications on the philosophy of mathematics and its practice.